Spectrum sensing algorithm based on average value of middle part of power spectral density - Zhijin ZHAO; Xi LV; Shilian ZHENG (Dianxin kexue)
The difference between maximum and minimum value of the received signal power spectrum is distinct when the primary user signal is present or absent.Using this characteristic,the spectrum sensing algorithm based on the average of the middle part of power spectral density was proposed.Since the minimum of the signal power spectral density fluctuated,the minimum couldn't be accurately estimated from a frequency point.The minimum value of the power spectrum was estimated by using the average value of the middle part of the received signal power spectrum to reduce the effect of the randomness of minimum value on spectrum sensing performance.The expressions of detection threshold and detection probability were derived.Simulation results show that performance of the algorithm is better than those of the present spectrum sensing algorithms based on power spectrum density under the AWGN channel and the Rayleigh fading channel.The algorithm didn't need the primary user information and complicated eigenvalue decomposition.